Theoretical approaches for understanding indigenous masculinities in Mexico - Díaz Cervantes, Rufino (2022)
This paper reflects on the gender perspective, historicization and decolonization as part of a theoretical-methodological proposal, to understand the gender systems that support masculinities and models of being a man, linked to reproduction and contemporary indigenous survival in Mexico. It constitutes a first effort of reflective analysis, on how to approach these ethnicized and gendered realities, specifically on masculinities and being a man. To do this, we start by discussing the contributions of some gender studies of men and masculinities, which do not constitute an exhaustive and updated review, but only an approximation to the growing knowledge base, to support the methodological proposal with which it seeks to understand the patriarchal, heterosexist and colonizing constraints on men and women of indigenous peoples. In this work, it is argued that re-readings of these realities are required through theoretical-methodological proposals that are sensitive to these realities, in order to stop the homogenizing views of the indigenous gendered subject, specifically the masculinized one from westernized gender systems.